Ensuring the price competitiveness of goods of a wholesale trade organization by optimizing logistics costs when transporting goods over long distances - A. Yu. Volkov (Путеводитель предпринимателя, 2023)
The article is devoted to the study of the prospects for the influence of logistics cost optimization processes on the possibility of ensuring the price competitiveness of goods of a wholesale trading organization using the example of the sale of craft beer. Aspects of the concept of competitiveness are clarified, as well as levels and factors (price and non–price) that determine competitiveness are identified. In this study, ensuring price competitiveness is disclosed in the structure of commodity competitiveness using the example of craft beer. The problems faced by the wholesale trading company when transporting craft beer over long distances are highlighted. The negative nature of the impact of these problems on the price competitiveness and image of the supplied craft beer is revealed. As an intermediate tool for ensuring the price competitiveness of craft beer, the methodology for transporting goods over long distances is considered. The mechanism and place of the methodology in the structure of ensuring price competitiveness is highlighted. The effects of the implementation of the technique in the conditions of a wholesale trading enterprise are disclosed.